استراتيجيات التدوين التاريخي لدى العرب - الربيعى، إسماعيل نوري مسير (جامعة بنغازي - كلية الآداب والعلوم بالمرج, 2015)
النظرة المتفحصة في البدايات التي رافقت ظهور التدوين التاريخي عند العرب، توضح وبجلاء التداخل بين نوعين من الرواية التاريخية، هما الرواية الشفوية التي تناقلته الألسن جيلا بعد جيل، وحملت بين ثناياها الكثير من المعطيات الخرافية، واستندت على العقلية الأسطورية، والمبالغة في تصوير الأحداث والفاعلين. والواقع أن المصدر الذي نبعت منه، قد تمثل في الفترة السابقة لظهور الإسلام، في حين أن النوع الثاني كان قد اعتمد على التدوين خلال القرن الثاني الهجري، وبهذا فإنه يعد الوليد الشرعي للتراكم المعرفي والثقافي داخل المجال العربي الإسلامي. ولعل السمة البارزة في هذا النوع استناده إلى الدقة العلمية التي فرضتها الظروف السياسية والإدارية للدول العربية الإسلامية، هذا بالإضافة إلى المؤثرات الفكرية التي فرضتها علاقات الجوار مع الحضارات الأخرى، والاتصال الكثيف مع الأمم والشعوب بحكم حركة الفتوحات. على الرغم من السمات الحضارية البارزة التي خلفتها الحواضر العربية في بلاد اليمن، خلال الفترة التاريخية السابقة لظهور الإسلام، وتوافر اللقي الأثارية والنقوش التي تعتبر المعين الأهم للدارسين والباحثين، على اعتبار المدون منها، وأنها تمثل شكلا من أنماط الكتابة، إلا أن الاضطراب والارتباك كان هو السائد في كل ذلك. إذ تتخذ الطابع الشكلي المستند إلى المبالغة في أخبار الملوك، يعتورها الابتسار والانتقال المفاجئ بين الحقب والمراحل التاريخية. وعلى هذا فإن الأخبار التي تقدمها هذه المدونات لا تبتعد كثيرا عن مضمون الروايات الشفوية.
The closer look at the very beginning that accompanied the emergence of blogging history when the Arabs, to clarify and clearly overlap between the two types of historical novel, two novel oral circulated tongues, generation after generation, and held the seat of many of the facts superstitious, and were based on mental legendary, and exaggeration in the portrayal of events and actors Indeed, the source from which it originated, may represent in the period prior to the advent of Islam, while the second type had relied on blogging during the second century AH, and thus it is a legitimate child of the accumulation of knowledge and cultural area within the Arab Muslim world. Perhaps the salient feature in this type introduced into the scientific accuracy imposed by the political and administrative conditions of the Arab and Islamic countries, in addition to the intellectual influences imposed by the neighborly relations with other civilizations, and communication-intensive with nations and peoples by virtue of the movement of conquests. Although features of the cultural landmark left by the Arab centers in the country of Yemen, during the historical period prior to the advent of Islam, and the availability of finds of archaeological and inscriptions which are designated the most important for scholars and researchers, since the blogger of them, and they represent a form of writing styles, but the turmoil and confusion was prevailing in all of this. In taking the formal nature of the document to exaggerate the news of the Kings, the maintenance level prematurity and sudden transition between eras and historical phases. On this, the news provided by these blogs do not stray much from the content of oral histories.
Keywords: التاريخ الإسلامي -- التأريخ -- التدوين -- الكتابة التاريخية